Anti-oxidant properties of ficus religiosa L. Bark extract on human keratinocytes - Dixit, Shailesh S.; Kulkarni, Atul; Seo, Hyo Hyun; Gadgil, Jayant; Dingre, Medini; Umar, Ahmad; Moh, Sang Hyun; Parasharami, Varsha A. (Science of Advanced Materials, 2016)
Ficus religiosa (Sacred Fig) is a medicinally important tree, native to the Indian subcontinent. It has been extensively pharmacologically researched species having wide spectrum of medicinal properties. All parts of F. religiosa tree are known to possess important medicinal properties such as anti-oxidant, anti-inflammatory, wound healing and skin diseases etc. However, effects of F. religiosa on skin cells line HaCaT was not studied for its antioxidant properties. In this report we have investigated F. religiosa bark aqueous extract for its antioxidant properties on human keratinocytes (HaCaT) cell line using DPPH, superoxide dismutase 1, superoxide dismutase 2 and catalase assay. We observed that F. religiosa bark aqueous extract efficiently scavenged (80%) DPPH radicals. Superoxide dismutase1 assay of F. religiosa bark aqueous extract effectively scavenged superoxide radicals (O-2(-)) and showed dose dependent activity. Reactive oxygen species were trapped by superoxide dismutase 2 assay of F. religiosa bark aqueous extract and form hydrogen peroxide. Catalase assay results revelled that hydrogen peroxide was further decomposed to give water and oxygen. Thus various anti-oxidant assays of F. religiosa bark aqueous extract indicate that it efficiently reduced the reactive oxygen species in skin cells.
Keywords: Anti-Oxidant; Catalase Assay; DPPH Assay; Ficus religiosa; Keratinocyte HaCaT Cell Line; Moraceae; SOD Assay

Spinel magnesium ferrite (MgFe2O4): a glycine-assisted colloidal combustion and its potentiality in gas-sensing application - Nadargi, Digambar; Umar, Ahmad; Nadargi, Jyoti; Patil, Jayvant; Mulla, Imtiaz; Akbar, Sheikh; Suryavanshi, Sharad (Chemosensors, 2022)
Herein, we describe the facile synthesis of spinel MgFe2O4 ferrite and its potential use as a gas sensor using a straightforward and reliable sol-gel approach, i.e., the glycine-assisted auto-combustion route. The novelty in obtaining the sensing material via the auto-combustion route is its inherent simplicity and capability to produce the material at an industry scale. The said cost-effective process makes use of simple metal salts (Mg and Fe-nitrates) and glycine in an aqueous solution, which leads to the formation of spinel MgFe2O4 ferrite. A single-phase crystallinity with crystallite sizes ranging between 36 and 41 nm was observed for the synthesized materials using the X-ray diffraction (XRD) technique. The porous morphologies of the synthesized materials caused by auto-ignition during the combustion process were validated by the microscopic investigations. The EDS analysis confirmed the constituted elements such as Mg, Fe, and O, without any impurity peaks. The gas-sensing ability of the synthesized ferrites was examined to detect various reducing gases such as LPG, ethanol, acetone, and ammonia. The ferrite showed the highest response (>80%) toward LPG with the response and recovery times of 15 s and 23 s, respectively. Though the sensor responded low toward ammonia (similar to 30%), its response and recovery times were very quick, i.e., 7 s and 9 s, respectively. The present investigation revealed that the synthesized ferrite materials are good candidates for fabricating high-performance sensors for reducing gases in real-world applications.
Keywords: Gas sensors; glycine combustion; MgFe2O4; reducing gases

Gas sensors and factors influencing sensing mechanism with a special focus on MOS sensors - Nadargi, Digambar Y. Y.; Umar, Ahmad; Nadargi, Jyoti D. D.; Lokare, Smita A. A.; Akbar, Sheikh; Mulla, Imtiaz S. S.; Suryavanshi, Sharad S. S.; Bhandari, Nagesh L. L.; Chaskar, Manohar G. G. (Journal of Materials Science, 2023)
Industrialization and its progress are very important for the economy and to move towards prosperity, stimulating innovation and creating jobs. Nonetheless, industrialization has negative impacts, if not done judiciously, such as pollution, increased greenhouse gas emissions, and global warming. Therefore, amenity-with-security is of fundamental significance in a new and dynamic lifestyle. A gas sensor is one of the crucial devices for monitoring and subsequently preserving the clean atmosphere among a number of other safety technologies. In-depth assessments of gas sensors and their necessity in the environment (air) pollution are provided in the current review. With a special emphasis on metal oxide semiconductor (MOS)-based gas sensors, the review includes a thorough study of gas sensors and the factors relating to sensing mechanisms. It not only describes the basic concepts and brief history of gas sensors, but also highlights the schemes responsible for improving the gas sensing properties and state-of-art literature review. These schemes include (1) surface engineering/morphological tuning and (2) bulk and surface doping. To keep scientific rigour and in-depth analyses, this review focuses on these two schemes only. In the doping area, the emphasis is given on graphene loading, decorated with nanoparticles of noble metals, spillover mechanism, and heterojunction (p-n, n-n, and p-p) formation. The conclusion summarizes the most optimized MOS gas sensors with enhanced gas sensing capabilities. The emphasis is given to formulate the article in such a way that it will be useful for the beginners who wish to explore the gas sensor research field, as well as to the established researchers to further improve the sensing capabilities of MOS gas sensors.

Green synthesis of GO-loaded Ag/ZnO nanocomposites for methyl orange degradation - Nadargi, Digambar Y.; Nadargi, Jyoti D.; Tamboli, Mohaseen S.; Tamboli, Asiya M.; Mulla, Imitaz S.; Umar, Ahmad; Truong, Nguyen Tam Nguyen; Suryavanshi, Sharad S. (Journal of Materials Science-Materials in Electronics, 2023)
Nature is a perfect laboratory for creating novel nanomaterials for a variety of applications. A robust green synthesis approach to GO-loaded Ag/ZnO nanocomposite materials using medicinal plant extraction and their potential application in methyl orange dye degradation are reported. The straightforward technique employs zinc and silver nitrate precursors in an aqueous solution of medicinal plant extract, causing the precipitation process. Prior to photocatalytic investigations, the physico-chemical properties of the material are analysed using TG-DTA, XRD, FE-SEM, TEM, EDAX and BET. The developed material showcase hexagonal wurtzite structure of ZnO, with face-centered-cubic phase of Ag and AgCl. All the samples exhibit aggregated, irregular rounded grains, as expected in the precipitation synthesis process. Pristine ZnO showed 15.5% degradation efficiency towards methyl orange, which was further improved by doping Ag from 0.5 to 2 mol%. The catalyst with 1 mol% Ag doping resulted in the better photocatalytic activity (26.30%), which has again improved by loading the GO (27.46%). The outcome of this study provides the new insights to GO-loaded Ag/ZnO nanocomposites by green synthesis route, in view of photocatalytic applications.